‫أﺛﺮ‬‫ﻛﻔﺎءة‬ ‫إدارة‬ ‫ﻣﻜﻮ‬ ‫ت‬ ‫اﻻﺣﺘﻴﺎج‬ ‫ﰲ‬ ‫رأس‬ ‫اﳌﺎل‬ ‫اﻟﻌﺎﻣﻞ‬ ‫ﻋﻠﻰ‬ ‫ﻣﺆﺷﺮات‬ ‫اﻷداء‬ ‫اﳌﺎﱄ‬ ‫ﰲ‬ ‫اﳌﺆﺳﺴﺔ‬‫اﻟﺼﻨﺎﻋﻴﺔ ‫دراﺳﺔ‬ ‫ﺣﺎﻟﺔ‬ ‫ﻣﻄﺎﺣﻦ‬ ‫ﺑﻠﻐﻴﺚ‬ ‫اﻟﻜﱪى‬ 2012-2016‫ﻟﻠﻔﱰة‬ - ﻋﻣﺎد‬ ‫اﻟدﯾن‫ ﺟوﯾﻣﻊ‬‫ ‬; ‬‫ﻣﺻﻌب‫ رزاق‬ (My University, 2018)
This study aimed to demonstrate the impact of working capital management efficiency on financial performance indicators of industrial companies. The study sample consist of BELGHIT Company of the period between 2012 - 2016. To analyze the study data we used statistical descriptive method: simple linear regression model analysis to testing hypotheses of the study with the Eviews 8 After processing and analyzing the study data and testing its hypothesis the study revealed a number of results that the efficiency of working capital management incarnate on the conversion to cash based on balance between dates of collection and payment ,this efficiency management is reflected in the balance of operating cycle and thus the financial balance situation of the company ,therefore the working capital management has a signicatif impact on the financial performance of the company by influencing the indicators of financial balance . In addition any efforts to increase the efficiency of the working capital management components, have a directly impact on the liquidity indicators, which reflect the ability of the payment company, how depends on liquidating inventory through efficient management and facilitating the collection of funds with the respect of collection and payment dates. In accordance with the Principe of profitability and profit to achieving results, efficient management of the components of working capital management requirement will necessarily cover funding requirements for the operating cycle. inancial performance indicators. ............................................................. دفت هذه الدراسة إلى بيان أثر كفاءة إدارة رأس المال العامل على الأداء المالي مؤشرات أداء الشركات الصناعية. تكونت عينة الدراسة من شركة بلغيت للفترة ما بين 2012 - 2016. لتحليل بيانات الدراسة استخدمنا المنهج الوصفي الإحصائي: نموذج الانحدار الخطي البسيط تحليل اختبار فرضيات الدراسة باستخدام برنامج Eviews 8 وبعد معالجة وتحليل بيانات الدراسة واختبار فرضيتها كشفت الدراسة عن عدد من وينتج عن ذلك أن كفاءة إدارة رأس المال العامل تتجسد في التحويل إلى نقد على أساس التوازن بين مواعيد التحصيل والدفع، وتنعكس إدارة الكفاءة هذه في الرصيد للدورة التشغيلية وبالتالي وضع التوازن المالي للشركة ومن ثم رأس المال العامل للإدارة تأثير كبير على الأداء المالي للشركة من خلال التأثير على مؤشرات التوازن المالي. بالإضافة إلى ذلك، فإن أي جهود لزيادة كفاءة مكونات إدارة رأس المال العامل قد تم تحقيقها مما يؤثر بشكل مباشر على مؤشرات السيولة التي تعكس قدرة شركة الدفع على الكيفية يعتمد على تصفية المخزون من خلال الإدارة الفعالة وتسهيل تحصيل الأموال فيما يتعلق بمواعيد التحصيل والدفع. وفقا لمبدأ الربحية والأرباح لتحقيق النتائج، والإدارة الفعالة لل إن مكونات متطلبات إدارة رأس المال العامل ستغطي بالضرورة التمويل متطلبات دورة التشغيل.